Effect of TiO2, Al2O3 and CaCO3 nano-additives in singular, binary and ternary forms on the mechanical, thermal and microstructural propertites of fly ash supplemented cement matrix. (2021) - Vanitha, N.; Revathi, T.; Gopalakrishnan, R.; Jeyalakshmi, R.
Highlights: The effect of the addition of different non-siliceous nano-materials on fly ash cement mortars is examined. The strength-enhancing effect increases with increasing volume of nanoadditives and is sustained for longer ages. The optimum ternary mixture of nanoadditives to be added to fly ash cement has been determined. Thermal conductivity values were found to decrease when nanoadditives were added in binary and ternary mixtures. Changes in the microstructure of the fly ash mortar has been examined through XRD pattern and SEM study. Abstract: In this paper, we focus on how nanoadditives such as nano-Al2 O3, nano-TiO2 and nano-CaCO3 modify the mechanical and capillary permeability of fly ash cement mortars (5:1). When nanoadditives are added in proportions of 2%, 4% and 6% of the binder volume, hydration products are generated, and thermal conductivity and microstructure of cement mortars undergo a change. Mechanical property measured at 7, 28 and 90 days are measured to understand the underlying pozzolanic reaction and filling effect. The experimental findings reveal that the form and quantity of refractory chemicals in mortar production had an impact hardened matrix at the early age between 7 and 28 days, but thereafter, there is only a marginal strength gain. Nano-Al2 O3 and nano-CaCO3 (at 2% of binder volume) additives were able to increase the mortar strength to the extent of 27% of the 28-day compressive strength at 7 days. The addition of 2% nano-TiO2 did not produce this effect. The addition of 6% nano-Al2 O3  + nano-CaCO3 in binary and 6% nano-TiO2  + nano-Al2 O3  + nano-CaCO3 blend in ternary combinations produced a phenomenally positive effect on the compressive strength with the reduction of capillary permeability at 90 days of setting. The X-ray diffraction patterns of these matrices compared with control showed a clear evidence of reduction of CH growth. Formation of a compact binding gel can be observed in scanning electron microscopic (SEM) pictures. A dense microstructure of binary and ternary nano additive mixes is establish to be favourable in decreasing the thermal conductivity of fly ash blend cement mortar measured at 30 °C. The combination of non-siliceous nano-size materials such as nano-Al2 O3, nano-TiO2 and nano-CaCO3 in small quantities have an impact on the pozzolanic reaction with continual strength gain and are effective in counteracting the shortcomings of fly ash blended with cement mortars.